2019
DOI: 10.1016/j.smallrumres.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Reducing mob size increases the survival of twin-born Merino lambs when feed-on-offer from pasture is limited and ewes are supplementary fed during lambing

Abstract: Reducing mob size increases the survival of twin-born Merino lambs when feed-on-offer from pasture is limited and ewes are supplementary fed during lambing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Dystocia, stillbirths, and starvationmismothering accounted for most mortalities which is consistent with other Australian studies [3,42]. Higher rates of mortality were observed for multiple-born lambs which is consistent with previous observations for predominantly mature ewe flocks [17,[43][44][45][46]; however, there was considerable variation in lamb mortality between birth and marking between flocks in this study. This may be explained by differences in genetics, environmental factors and other management factors (e.g., mob size and supplementary feeding) on lamb survival [3,43,47,48].…”
Section: Discussionsupporting
confidence: 92%
“…Dystocia, stillbirths, and starvationmismothering accounted for most mortalities which is consistent with other Australian studies [3,42]. Higher rates of mortality were observed for multiple-born lambs which is consistent with previous observations for predominantly mature ewe flocks [17,[43][44][45][46]; however, there was considerable variation in lamb mortality between birth and marking between flocks in this study. This may be explained by differences in genetics, environmental factors and other management factors (e.g., mob size and supplementary feeding) on lamb survival [3,43,47,48].…”
Section: Discussionsupporting
confidence: 92%
“…However, variation in the effect of mob size on lamb survival was observed in intensive experimental work conducted in two contrasting seasons. The survival of twin lambs decreased by 4% per additional 100 ewes in the mob when herbage mass was below 390 kg DM/ha and ewes were trail fed supplements during lambing (Lockwood et al 2019a), whereas the survival of single-and twin-born lambs was not observed to differ between mob sizes of 50 and 130 ewes when herbage mass at lambing exceeded 2400 kg DM/ha (Lockwood et al 2019d). This suggests that the effect of mob size on lamb survival could be influenced by herbage mass and supplementary feeding.…”
Section: Lamb Survivalmentioning
confidence: 99%
“…It would be of interested to determine if the same effect would be observed with lick feeders. Hinch and Brien (2014) stated that the limited data available suggests maximum flock sizes of 100-250 and 200-500 for twin and singleton-bearing ewes respectively, however, the optimal mob sizes are likely to be significantly smaller than this based on the recent work by Lockwood et al (2019aLockwood et al ( , 2019bLockwood et al ( , 2019cLockwood et al ( , 2019d and no such recommendations are available for triplets. Given the potential for many triplet lambs to be born in a short space of time, at a preferred lambing site, the impact of stocking rate and especially mob size on triplet survival requires investigation.…”
Section: Lamb Survivalmentioning
confidence: 99%
“…Primiparous ewes may be more susceptible to infectious diseases, as younger ewes are less likely to have developed immunocompetency to infection prior to pregnancy [ 21 , 22 ]. Most recent Australian studies that included lamb necropsies were conducted with multiparous ewes, and cause of death was assigned based on gross post-mortem findings without adjunct laboratory investigation [ 2 , 23 27 ]. In general, relatively few investigations for abortion and perinatal lamb death are submitted to veterinary diagnostic laboratories for exclusion of infectious diseases [ 12 ].…”
Section: Introductionmentioning
confidence: 99%